DINAMIKA DISKUSI (TALK) DALAM METODE TTW UNTUK MEMANTIK IDE MENULIS CERITA FANTASI: STUDI KASUS DI KELAS VII SMP N 6 MADIUN - Eriana Widya R; Jeffry Handhika; Muh. Waskito Ardhi (An Nafi': Multidisciplinary Science, 2026)
The Talk phase in the TTW (Think-Talk-Write) method is a critical bridge between individual idea incubation and text production. This study aims to describe the dynamics of student discussions in the Talk phase to spark ideas for writing fantasy stories in class VII of SMP Negeri 6 Madiun. This research uses a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews with students and teachers, and analysis of student discussion notes and fantasy story drafts. Thematic data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The findings show that the dynamics of discussion in the Talk phase are characterized by (1) collaborative idea exploration, where students build on each other's initial ideas, (2) negotiation of fantasy elements to maintain narrative logic, and (3) the emergence of peer validation that boosts confidence in developing unconventional ideas. Effective dialogue facilitators, both teachers and peers, play a key role in creating a safe and productive discursive space. This study concludes that the Talk phase is not just an idea-sharing session, but a collaborative cognitive process that enriches imagination, tests idea plausibility, and provides the social support needed for students to dare to write fantasy.